2016
DOI: 10.1016/j.ejca.2016.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and mortality of gynaecological cancers: Secular trends in urban Shanghai, China over 40 years

Abstract: Aim Appraisal of cancer trends is essential for future cancer control, but relevant studies in China are scarce due to a lack of long-term data. With 40-years of cancer registry data, we sought to evaluate secular time trends in incidence and mortality of gynecological cancers in an urban Chinese population. Materials and methods Data on incidence and mortality of invasive cervical, uterine and ovarian cancer were collected by the Shanghai Cancer Registry. Age-standardized incidence and mortality rates were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…4,17,18 In some countries, the trends were stable, 19Y22 whereas in others they increased. 23,24 The decreasing incidence trends in Ireland, NI (since 1998), and Israeli Jews are in accordance with observations for other high-background-incidence countries (eg, the United States). Decreases in incidence may be the result of a change in the structure of a population 4 ; however, they most likely reflect changing patterns of certain exposures.…”
Section: Incidence Trendssupporting
confidence: 85%
See 1 more Smart Citation
“…4,17,18 In some countries, the trends were stable, 19Y22 whereas in others they increased. 23,24 The decreasing incidence trends in Ireland, NI (since 1998), and Israeli Jews are in accordance with observations for other high-background-incidence countries (eg, the United States). Decreases in incidence may be the result of a change in the structure of a population 4 ; however, they most likely reflect changing patterns of certain exposures.…”
Section: Incidence Trendssupporting
confidence: 85%
“…23,54,55 In most other countries, mortality rates are decreasing 4,18,19,56 or stable. 17,23,54 The current study showed significantly decreasing mortality trends during the period 1994Y2013 in Ireland, NI (since 2005), and Israeli Jews, which are consistent with the observations for other high-background-mortality countries (ie, the United States, for the period 1975Y2011).…”
Section: Mortality Trendsmentioning
confidence: 99%
“…Imbalance of economic development and diversity of lifestyles contribute to apparent differences in the incidences and mortalities of cancer types in different areas of China. Although estimates of cancer burden in China have been reported, the assumptions are limited to a snapshot of the patterns by cancer site in a given year [ 3 6 ] or to longitudinal situations of specific cancers and all cancer types for relatively short durations [ 7 11 ], making comparisons of long-term trends across all cancer types in accordance with economic development and lifestyle changes difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian cancer mortality from 1979-2010 has remained stable in Hong Kong and Singapore, although it increased in South Korea (Lee et al, 2014). In Shanghai, China, over a 40-year period, ovarian cancer incidence has increased on average 1.8% per annum (Huang et al, 2016). A study in Niigata prefecture also showed increasing rates of ovarian cancers, and in particular for mucinous and clear cell adenocarcinomas (Yahata et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Internationally, it is the 7th most common cancer among women, contributing 2.4% of all incident cases of cancer among women, and accounting for 4.4% of all cancer deaths (International Agency for Research in Cancer [IARC], 2012). In many countries across Asia, the incidence of ovarian cancer has been rising (Lee et al, 2014;Huang et al, 2016). In Singapore, ovarian cancer is the 5th most common female cancer, constituting 5.4% of new cancer cases and 5.1% of all female cancer deaths.…”
Section: Introductionmentioning
confidence: 99%